The knowledge and practice of pediatricians in children's oral health: a scoping review - Virginia Dickson-Swift; Amanda Kenny; Mark Gussy; Colleen McCarthy; Stacey Bracksley-O'Grady (BMC, 2020)
Abstract Background Dental caries is a significant public health problem and one of the most common chronic conditions affecting children. The potential for the non-dental workforce to improve children's oral health is well documented. For well over a decade, there have been calls for pediatricians to address children's oral health, but the incorporation of oral health screening, referral, and oral healthcare in pediatric practice remains underdeveloped. Developing action to strengthen the role of pediatricians' in children's oral health requires an understanding of their current knowledge and practice. In this scoping review, we aimed to comprehensively map what is known about the knowledge and practice of pediatricians regarding children's oral health. Methods Arksey & O'Malley's five-stage review process was used to comprehensively map studies undertaken on pediatrician's knowledge and practice regarding children's oral health. Key search terms were developed and a total of 42 eligible articles are included in the review. Results The studies were conducted in 19 countries. The majority (41/42) were quantitative, with over 90% using self-reported surveys. Only four studies used previously validated survey tools, with most adapting questions from previous studies. Observational designs were used in two studies and one used qualitative methods. Sample size ranged from 15 to 862. Oral health knowledge amongst pediatricians was reported to be mostly poor, with many gaps in key areas including age for first dental visit, dental caries and oral health risk assessments. Studies on the translation of oral health knowledge to practice were limited, with wide variation in rates of assessment. Few studies assessed actual practice. Conclusions This scoping review highlights growing international interest in the role of pediatricians in children's oral health. Findings demonstrate that pediatricians have limited knowledge and understanding in critical areas, including; initial clinical signs of dental caries, recommended age for first dental visit, etiology of dental caries and recommended use of fluorides. Barriers for pediatricians include inadequate education and training, time constraints in practice and lack of referral pathways. Development of a validated tool to assess knowledge and practice is needed. This review provides a starting point to guide future research and areas for systematic reviews.